Maximizing Leaves, Inflorescences, and Chemical Composition Production of Moringa oleifera Trees under Calcareous Soil Conditions - Amira K. G. Atteya; Aishah N. Albalawi; Hala M. Bayomy; Eman S. Alamri; Esmail A. E. Genaidy (Plants, 2022)
One of the main issues limiting plant productivity is a lack of soil nutrient resources, especially in calcareous soil, which covers more than one third of the world’s land surface area. On the other hand, despite rising demand for all parts of the Moringa oleifera tree, several studies have focused on its leaf production as an herbaceous plant, rather than as a tree, and no extensive research has been carried out on leaf and inflorescence production in the mature tree. As a result, the influence of vermicompost and NPK (minerals and nanoparticles), as well as their combination, under calcareous soil conditions, was investigated in this study. The experiment was set up as a split plot in Randomized Complete Block Design (RCBD) with three replicates. In both seasons considered in this study, it was discovered that increasing the quantity of vermicompost and employing NPK fertilization, as well as their combination treatments, greatly enhanced all parameters and yield of distinct Moringa oleifera tree parts. Furthermore, the combination treatment T21 yielded the highest mean values of growth, leaves, and chemical composition parameters, as well as the highest yield from the Moringa oleifera tree. In both seasons, the highest number of inflorescences per tree, as well as the yield of fresh and dry inflorescences, was measured using combination treatment T18. In both seasons, however, increasing the level of vermicompost, NPK, and their combination treatments significantly reduced the total phenolic and flavonoid content and antioxidant activity of dry Moringa oleifera leaves.